Deciphering the Antibacterial Mode of Action of Alpha-Mangostin on Staphylococcus epidermidis RP62A Through an Integrated Transcriptomic and Proteomic Approach - Sivaranjani, Murugesan; Leskinen, Katarzyna; Aravindraja, Chairmandurai; Saavalainen, Päivi; Pandian, Shunmugiah Karutha; Skurnik, Mikael; Ravi, Arumugam Veera (Frontiers in Microbiology, 2019)
Background: Alpha-mangostin (α-MG) is a natural xanthone reported to exhibit rapid bactericidal activity against Gram-positive bacteria, and may therefore have potential clinical application in healthcare sectors. This study sought to identify the impact of α-MG on Staphylococcus epidermidis RP62A through integrated advanced omic technologies. Methods: S. epidermidis was challenged with sub-MIC (0.875 µg/ml) of α-MG at various time points and the differential expression pattern of genes/proteins were analysed in the absence and presence of α-MG using RNA sequencing and LC-MS/MS experiments. Bioinformatic tools were used to categorize the biological processes, molecular functions and KEGG pathways of differentially expressed genes/proteins. qRT-PCR was employed to validate the results obtained from these analyses. Results: Transcriptomic and proteomic profiling of α-MG treated cells indicated that genes/proteins affected by α-MG treatment were associated with diverse cellular functions. The greatest reduction in expression was observed in transcription of genes conferring cytoplasmic membrane integrity (yidC2, secA and mscL), cell division (ftsY and divlB), teichoic acid biosynthesis (tagG and dltA), fatty-acid biosynthesis (accB, accC, fabD, fabH, fabI and fabZ), biofilm formation (icaA) and DNA replication & repair machinery (polA, polC, dnaE and uvrA). Those with increased expression were involved in oxidative (katA and sodA) and cellular stress response (clpB, clpC, groEL and asp23). The qRT-PCR analysis substantiated the results obtained from transcriptomic and proteomic profiling studies. Conclusions: Combining transcriptomic and proteomic methods provided comprehensive information about the antibacterial mode of action of α-MG. The obtained results suggest that α-MG targets S. epidermidis through multifarious mechanisms, and especially prompts that loss of cytoplasmic membrane integrity leads to rapid onset of bactericidal activity.